PENGARUH PERPUTARAN PIUTANG, PERPUTARAN PERSEDIAAN DAN PERPUTARAN KAS TERHADAP PROFITABILITAS (Studi Kasus pada Perusahaan Manufaktur Sub Sektor Otomotif dan Komponen yang Terdaftar di Bursa Efek Indonesia Tahun 2016 – 2018) - Mimi Yetri; Rahmawati Rahmawati (Jurnal Riset Manajemen Indonesia, 2020)
This research was conducted with the aim of examining the effect accounts receivable turnover, inventory turnover and cash turnover on profitability and variables that influencethe firm value of automotive sub-sector manufacturing companies and components listed on the Indonesia Stock Exchange in 2016-2018. The population in this study are companies listed on the automotive sub-sector manufacturing companies and components listed on the Indonesia Stock Exchange in 2016-2018, which are 13 companies. The technique used in sampling is the purposive sampling method, the sampel in this study was selected as many as 12 companies. Hypothesis testing uses multiple linear regression analysis with the help of SPSS 23.00 for windows. The results of the study show that simultaneously influence of accounts receivable turnover, inventory turnover and cash turnover affect the profitability. Partially cash turnover has an effect on profitability.